Analisa Efektivitas Pilot Project Dalam Perubahan Transformasional - Kania Mayasari (UMSurabaya Publishing, 2020)
ABSTRACT To improve company performance, Senior Executives took the initiative to make a transformational change as a competitive business strategy. Performance is formed by employee productivity. This change began with a pilot project before it went into national roll-out. Pilots are chosen from the sales force. This study aims to analyze the effectiveness of the pilot project for 5 months to 102 Change Agent Candidates (CAC). Research is descriptive, analyzing quantitative data. The project resulted in significant productivity growth, an increase of 33.7% with a turnover of 0.9%. Case count productivity penetrated 10.14 from target 9. Its success cannot be separated from the role of Senior Executives who provide strong engagement. With this success, transformational change can be implemented nationally. Keywords : effectiveness; pilot project; transformational change ABSTRAK Untuk memperbaiki performa perusahaan, Eksekutif Senior berinisiatif melakukan perubahan transformasional sebagai strategi bisnis yang kompetitif. Performa terbentuk dari produktivitas karyawan. Perubahan ini diawali dengan pilot project sebelum berlaku nasional. Pilot dipilih dari tenaga pemasaran. Penelitian ini bertujuan untuk menganalisis efektivitas pilot project selama 5 bulan kepada 102 Change Agent Candidate (CAC). Penelitian bersifat deskriptif, menganalisis data kuantitatif. Project menghasilkan pertumbuhan produktivitas yang signifikan, meningkat 33,7% dengan turn over 0,9%. Produktivitas case count menembus 10,14 dari target 9. Kesuksesannya tidak lepas dari peran Eksekutif Senior yang memberikan engagement yang kuat. Dengan keberhasilan ini, perubahan transformasional dapat diberlakukan secara nasional. Kata kunci : efektivitas; pilot project; perubahan transformasional